Analysis of Moving Average Convergence Divergence (MACD) in different economies - Pandit, Zayd (2013)
The current dissertation is undertaken to analyze technical analysis, its indicators and their profitability and feasibility. This dissertation gives the basics idea of technical analysis and how it works and helps the investors in generating profits. It also shows how to use charts for technical analysis. In the analysis part it focuses on one of the most popular indicator called Moving Average Convergence Divergence (MACD) and applies it in different stock exchanges to examine whether it works in all or not. The objective of this dissertation is to provide investors with a clearer view of where to use Moving Average Convergence Divergence (MACD). This dissertation analyses performance of Moving Average Convergence Divergence in five different stock markets. These stock markets include Bombay Stock Exchange, Athens Stock Exchange, New York Stock Exchange, Dubai Financial Market, Abu Dhabi Stock Exchange and Australian Stock Exchange. The conclusion of this dissertation was that Moving Average Convergence Divergence was able to work at its best where the economy was not going through any kind of crisis. In other words efficient markets where as it was not able to generate much profit in economy like Greece which is suffering from European Debt Crisis. In Middle Eastern markets it was not able to perform well at all. At the end of this paper investors can easily make out where they can use MACD and where they need to use fundamental analysis or other technical indicators.